Occupational Gender Bias Revisited: Methodological Improvements - Ratzlaff, Harold C.; Kahn, Sharon E. (Canadian Journal of Counselling and Psychotherapy, 2012)
To investigate counsellor bias in occupational choice for female students, six short fictitious case studies were employed that could describe either a male or a female subject. One hundred fourteen randomly selected high-school counsellors chose occupations that paid less and required more supervision for female thanfor male case study subjects. The design and statistical analyses are presented anddiscussed in response to criticisms of research reported in counselling journals. The methodology used in the present study is suggested as being appropriate for investigations of responses to case studies where designated gender is the stimulus variable.